THE IMPACT OF TRADITIONAL GAMES ON THE SOCIAL SKILLS OF ELEMENTARY SCHOOL STUDENTS IS REVIEWED FROM A GENDER PERSPECTIVE - Ridha Nuranisa; Lutfi Nur; Rafdlal Saeful Bakhri (Universitas Majalengka, 2026)
Developing elementary school students' social skills is an important objective of physical education; however, studies examining traditional games while considering gender characteristics remain limited. This study aimed to analyze the effect of traditional games and gender on the social skills of elementary school students. A quasi-experimental study employing a 2 × 2 pretest-posttest factorial design was conducted involving 52 fifth-grade elementary school students who were divided into four treatment groups based on traditional game type and gender. The treatments were conducted through the traditional games of boy-boyan and bakiak. Data were collected using a social skills questionnaire covering communication, cooperation, assertion, responsibility, empathy, engagement, and self-control. Data analysis was conducted using descriptive statistics, prerequisite tests, and two-way analysis of variance followed by a post hoc comparison test. The results revealed a significant main effect of traditional game type on students' social skills (F(1.48) = 69.447, p = 0.001, η²p = 0.591), indicating that students participating in boy-boyan demonstrated higher social skill scores than those participating in bakiak. Gender also significantly affected social skills (F(1.48) = 4.506, p = 0.039, η²p = 0.086). Furthermore, a significant interaction effect between traditional game type and gender was found (F(1.48) = 107.694, p = 0.003, η²p = 0.692). This study contributes to the literature by providing empirical evidence regarding the interaction between traditional game type and gender in shaping elementary school students' social skills, an area that has received limited attention in previous traditional game research. These findings suggest that traditional games can be effectively integrated into physical education programs to enhance students' social development while considering gender-related characteristics.